Análisis de la gestión del talento humano del Patronato Provincial de Chimborazo y su incidencia en el desarrollo institucional 2013-2014. - Miranda Almachi, Verónica Elizabeth (2016)
The purpose of this research was to analyze the management of human talent in the Provincial Board of Chimborazo and how this affects the institutional development during the 2013-2014.It started with the inclusion of General aspects of the institution by specifying their most relevant characteristics, then proceed with the theoretical foundation of the study variables. The hypothetical deductive method was used in establishing a hypothesis subject to verification from a general perspective to infer results in the situation of the human talent in the institution. The research designed was documentary bibliographic sources was required to link them with the internal and external aspects taking place in the Board. Information was obtained directly from the population at the site where they do their activities. The results obtained through collection techniques such as survey and interview techniques are displayed in tables and graphs statistics that they are analyzed and interpreted by comparing them with the theoretical framework. The conclusions refer to the proposed objectives and of these departed the recommendations, which are aimed at those responsible for the management of human talent to optimize people and contribute to the institutional development. An improvement plan for the management of human talent is finally proposed.